Escalonamento inteligente do consumo de energia elétrica em função de diferentes imposições de conforto térmico e aproveitamento de energia solar - Fonseca, André Luiz Amorim da (2022)
From the technological development around the world, new solutions are sought for better use of natural resources, including the resources that serve as a source of electricity generation. One of the most efficient ways to reduce demand in the residential sector in the context of smart grids is using Demand Response methods, which are responsible for directly or indirectly controlling the use of electricity in buildings. However, consumption scheduling modules have only considered air conditioning equipment to achieve thermal comfort or leave aside the concern with maintaining this condition of the occupants. From this, the main objective of this thesis is to build and analyze the application of residential electricity consumption scheduling for demand response programs, considering the tariff modality named as white tariff. The proposal simultaneously considers the maintenance of thermal comfort, the use of photovoltaic and thermal solar energy, the management of the residential battery, and consumption scheduling to minimize the daily electricity costs. Thus, the work considered a residence produced with premises of bioclimatic architecture suitable for the climate of each of the eight Brazilian bioclimatic zones. In a second step, different scenarios of the white hourly tariff were evaluated in comparison to conventional tariffs. To obtain residential consumption parameters, public research data related to equipment ownership and consumption habits in Brazil were used. The approach proposes the use of the Givoni bioclimatic chart for hot developing countries as a decision mechanism between the air conditioning alternatives to be used as an input parameter in a problem of optimization of the scheduling consumption of household appliances throughout the day, as well as the energy exchange of the battery with the grid and the photovoltaic and thermal solar use. The results found in the tests indicate the feasibility of the proposed solution for most of the days analyzed, obtaining up to 100% savings, that is, situations in which a null value of the daily cost is obtained, leaving portions of electricity consumption to be compensated. The use of solar energy within the proposal reinforces the importance of this energy type and indicates which cities and climatic conditions the proposed mechanism is most suitable for.